DARI METOBU HINGGA MEKAMBO: PERTUMBUHAN PEMUKIMAN KOTA KOLAKA PADA ABAD XX - Melamba, Basrin (History Department, Semarang State University and Historian Society of Indonesia, 2013)
This paper describes the growth of Kolaka city in Bone in XX century. In early XX century, Kolaka became the capital of onderafdeeling Kolaka since 1911. In 1912 indirectly the influence of this policy was the development and repair of city facilities in the form of port medium, warehouse, office of toll and duty, and road network in Kolaka. Those settlement growths in Kolaka affected the economic activity and commerce. The settlement and physical region got much better especially after Dutch government settled the resident settlement with the settlement model following the centripetal roadway pattern with the village (kampung) pattern (oÃ¢â‚¬â„¢kambo). The resident settlement pattern also followed the coastline of Mekongga and Bone Bay. Exploiting the nickel mine yielded the urban symptom in the center of area of nickel mining. Key words: growth, settlement, Kolaka cityÃ‚Â Makalah ini menjelaskan tentang pertumbuhan Kota Kolaka di Bone pada abad XX. Pada awal abad XX, Kolaka menjadi ibukota daerah setingkat kabupaten (onderafdeeling) Kolaka sejak tahun 1911. Pada tahun 1912 secara tidak langsung pengaruh dari kebijakan ini adalah adanya pengembangan dan perbaikan fasilitas kota dalam bentuk sarana pelabuhan, gudang, kantor tol dan pajak, serta jaringan jalan di Kolaka. Pertumbuhan pemukiman di Kolaka tersebut mempengaruhi kegiatan ekonomi dan perdagangan. Pemukiman dan fisik wilayah menjadi jauh lebih baik terutama setelah Pemerintah Belanda menyelesaikan pemukiman penduduk dengan model pemukiman yang mengikuti pola jalan sentripetal dengan pola kampung (o'kambo). Pola pemukiman penduduk juga mengikuti garis pantai Teluk Mekongga dan Bone. Memanfaatkan tambang nikel juga menghasilkan gejala urban di tengah area pertambangan nikel.Kata kunci: pertumbuhan, pemukiman, kota Kolaka